Level of surgical complexity in mandibular third molars evaluated by panoramic radiographs in a public hospital in Lima - Lilibeth Zea Rojas, Karen (2024)
Objectives: Determine the level of surgical complexity of mandibular third molars (3MM) evalued by panoramic radiographs (PAN) in a public hospital in Lima and whether it was associated with sex, age, and type of molar tooth. Materials and Methods: The 3MM sample was 289 observed in 266 PAN digital of adults ≥18 years (50.2% men, mean age: 36.44±14.86 years). The eight parameters of the Pernambuco index were: age, body mass index (18.5-24.9 or ≥25), level of the occlusal plane, available retromolar space, angle of impact, root curvature, number of roots and relationship with the 2MM. Statistic analysis was performed with the chi-square, Mann-Whitney U and Kruskal-Wallis tests. Results: The 3MM had a moderate level of surgical complexity (54.7%) followed by mild (40.1%). The majority presented vertical impaction (48.8%), dilaceration (82.7%), two or more roots (58.8%) and contact with the 2MM crown (72.0%). A mild complexity was related to women and a higher age, while a severe level was related to men and a younger age (p=0.01 [sex], p=0.009 [age]). The index was higher in men (14 [IQR=4]) than women (13 [IQR=2]) and was slightly negatively correlated with age (rho=- 0.239). Conclusions: The level of surgical complexity of 3MM of Peruvian adults was moderate, mainly associated with vertical impaction, dilacerated root curvature, a greater number of roots and contact with the crown of the 2MM. The complexity was symmetrical on sides but varied according to sex and age. Greater complexity was observed in men and at younger ages.